Thyroid cancer cell lines: an overview - Saiselet, Manuel; Floor, Sebastien; Tarabichi, Maxime; Dom, Geneviéve; Hébrant, Aline; van Staveren, Wilma; Maenhaut, Carine (Frontiers in Endocrinology, 2012)
Human thyroid cancer cell lines are the most used models for thyroid cancer studies. They must be used with detailed knowledge of their characteristics. These in vitro cell lines originate from differentiated and dedifferentiated in vivo human thyroid tumours. However, it has been shown that mRNA expression profiles of these cell lines were closer to dedifferentiated in vivo thyroid tumours (anaplastic thyroid carcinoma, ATC) than to differentiated ones. Here an overview of the knowledge of these models was made. The mutational status of six human thyroid cancer cell lines (WRO, FTC133, BCPAP, TPC1, K1 and 8505C) was in line with previously reported findings for ten genes frequently mutated in thyroid cancer. However, the presence of a BRAF mutation (T1799A: V600E) in WRO questions the use of this cell line as a model for follicular thyroid carcinoma. Next, to investigate the biological meaning of the modulated mRNAs in these cells, a pathway analysis on previously obtained mRNA profiles was performed on five cell lines. In five cell lines, the MHC class II pathway was downregulated and in four of them, ribosome biosynthesis and translation pathways were upregulated. mRNA expression profiles of the cell lines were also compared to those of the different types of thyroid cancers. Three datasets originating from different microarray platforms and derived from distinct laboratories were used. This meta-analysis showed a significant higher correlation between the profiles of the thyroid cancer cell lines and ATC, than to differentiated thyroid tumors (i.e. PTC or FTC) specifically for DNA replication. This already observed higher correlation was obtained here with an increased number of in vivo tumours and using different platforms. In summary, this would suggest that some PTC or FTC cell lines (i.e. TPC-1) might have partially lost their original DNA synthesis/replication regulation mechanisms during their in vitro cell adaptation/evolution.